Linguistic consideration of texts in internet - P V Moroslin (Vestnik Rossijskogo universiteta družby narodov. Seriâ Lingvistika, 2009)
The research deals with linguistic and cultural approaches in considering the texts in the Internet. Different types of texts are examined as well as a process and results of semantic and cultural relations among the texts in the Internet are analyzed.